MARKETING STRATEGY AT LAKESSI MARKET IN PAREPARE, SOUTH SULAWESI DURING THE COVID 19 PANDEMIC - Besse Faradiba (Universitas Muhammadiyah Kalimantan Timur, 2021)
This study aims to determine the effect of marketing strategy and service quality on business competition at Lakessi Market during the Covid 19 pandemic. The measurement of marketing strategy in this study was carried out because people's purchasing power was weakening so that a marketing strategy was needed to gain profits during the Covid 19 period. Research method This method uses convenience sampling or purposive sampling where the proportional quota is 50 respondents. Analysis of the data used is descriptive analysis to describe the symptoms of the research results, while to see the effect of marketing, service quality on business competition in the Lakessi Parepare Market (quantitative data) using multiple linear regression analysis tools. The results show that marketing strategy has no effect on business competition and service quality has a positive effect on business competition and then significantly on business competition by 76.2%. For business actors (traders) it is expected to pay more attention to service quality because from the results of research on service quality which is very influential on business competition during the Covid-19 period, if they can excel in business competition, traders will get a bigger profit.